Hydrogen storage for micro-grid application: a framework for ranking fuel cell technologies based on technical parameters - John Adetunji Adebisi; Iheanacho Henry Denwigwe; Olubayo Moses Babatunde (Institute of Advanced Engineering and Science, 2023)
To securely address energy shortage and various environmental issues attributed to fossil fuel, the adoption of renewable energy is growing across the globe. However, wind and solar which form the bulk of the emerging renewable energy for micro-grid applications are intermittent and need energy storage device for backup. Due to its environmentally friendly nature, the use of hydrogen as storage mechanism is now being explored for micro-grid applications. However, due to the various technical criteria attributed to various fuel cell (FC) technologies used for hydrogen production, selecting the most suitable alternative remains a challenge. This study uses evaluation based on distance from average solution, a multicriteria decision making tool to rank FC technologies that can be used to produce of hydrogen energy storage in micro-grid applications. The analysis was based on 4 FC technologies and 6 technical criteria. The results of the study show that the most preferred FC technology for micro-grid application is the polymeric electrolyte membrane while the least preferred is molten carbonate FC. It is expected that future analysis would explore the inclusion of socio-economic criteria in the evaluation of the most preferred FC technology for micro-grid application.